2013 46th Hawaii International Conference on System Sciences 2013
DOI: 10.1109/hicss.2013.157
|View full text |Cite
|
Sign up to set email alerts
|

Culture Matters: Factors Affecting the Adoption of Telemedicine

Abstract: 1The present research investigates the influence of culture on telemedicine adoption and patient information privacy, security, and policy. The results, based on the SEM analysis of the data collected in the United States, demonstrate that culture plays a significant role in telemedicine adoption. The results further show that culture also indirectly influences telemedicine adoption through information security, information privacy, and information policy. Our empirical results further indicate that informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Indeed, a recent study showed a decrease in the attendance of non-English speakers after the implementation of telemedicine (46). Furthermore, a 2013 survey from Mansouri-Rad et al, demonstrated that the adoption of telemedicine was heavily in uenced by cultural norm (47). As none of the patients that were interviewed were CALD, this study is not able to explore the attitudes of this particular group.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, a recent study showed a decrease in the attendance of non-English speakers after the implementation of telemedicine (46). Furthermore, a 2013 survey from Mansouri-Rad et al, demonstrated that the adoption of telemedicine was heavily in uenced by cultural norm (47). As none of the patients that were interviewed were CALD, this study is not able to explore the attitudes of this particular group.…”
Section: Discussionmentioning
confidence: 88%
“…Besides, [88]demonstrated that security had a good and direct impact on the implementation of E-commerce [89]. According to [90], security had a significant and positive influence on M-commerce acceptance. [91] Thus, privacy is counted as a high major element in the implementation of E-commerce.…”
Section: Relative Importance and Total Contributionmentioning
confidence: 98%
“…Patient education can be challenging and relies on multiple factors including but not limited to provider training, patient and/or caregiver level of technological knowledge and education, as well as a diverse number of cultural factors and expectations. [ 55 56 57 58 59 60 61 ] The safety and quality of home-based care and self-monitoring depend on patient and/or caregiver understanding of the disease and the ability to practically and efficiently use the tele-presence tools at their disposal. In this context, good patient education requires a supportive learning environment, and the ability to individualize instructions to the patient's needs, level of understanding, general comfort with applicable technology, among other factors and expectations.…”
Section: Initiation Of At-home Services Including Technological and mentioning
confidence: 99%